2020
DOI: 10.1016/j.biopsych.2019.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics Profile in Depression: A Pooled Analysis of 230 Metabolic Markers in 5283 Cases With Depression and 10,145 Controls

Abstract: Background: Depression has been associated with metabolic alterations, which adversely impact cardiometabolic health. Here, a comprehensive set of metabolic markers, predominantly lipids, was compared between depressed and non-depressed persons. Methods: Nine Dutch cohorts were included, comprising 10,145 controls and 5,283 persons with depression, established with diagnostic interviews or questionnaires. A proton nuclear magnetic resonance metabolomics platform provided 230 metabolite measures: 51 lipids, fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
134
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 167 publications
(154 citation statements)
references
References 54 publications
18
134
2
Order By: Relevance
“…However, these authors highlighted that depression and lipid dysregulation could emerge from a shared etiology because genomewide association studies have reported a significant association between triglycerides and depression, and the BMI and depression. 21 Potentially consistent with this hypothesis and with the findings of the present study, in studies of patients receiving statins to prevent heart disease, the use of any statin reduced the odds of developing depression in comparison to individuals not using statin medications. 22 Moreover, a recent meta-analysis concluded that statins significantly reduced depression severity relative to placebo administration in patients with major depressive disorder.…”
Section: Discussionsupporting
confidence: 87%
“…However, these authors highlighted that depression and lipid dysregulation could emerge from a shared etiology because genomewide association studies have reported a significant association between triglycerides and depression, and the BMI and depression. 21 Potentially consistent with this hypothesis and with the findings of the present study, in studies of patients receiving statins to prevent heart disease, the use of any statin reduced the odds of developing depression in comparison to individuals not using statin medications. 22 Moreover, a recent meta-analysis concluded that statins significantly reduced depression severity relative to placebo administration in patients with major depressive disorder.…”
Section: Discussionsupporting
confidence: 87%
“…Metabolites (Metabolomic clock). Metabolite measurements have been described in detail previously 18,47 . In short, a total of 232 metabolites or metabolite ratios were reliably quantified from Ethylenediaminetetraacetic acid plasma samples using targeted high-throughput proton Nuclear Magnetic Resonance ( 1 H-NMR) metabolomics (Nightingale Health Ltd, Helsinki, Finland) 48 .…”
Section: Gene Expression (Transcriptomic Clock) Rna Processing and Amentioning
confidence: 99%
“…In regard to depression, we tested associations between the six SSRI-related metabolites and depressed mood in participants not prescribed an antidepressant drug (ATC code, N06A) 77 . Depressed mood was measured by either diagnostic interviews or validated depression questionnaires (n = 3,966 cases and n = 8,887 controls in the meta-analysis).…”
mentioning
confidence: 99%
“…Depressed mood was measured by either diagnostic interviews or validated depression questionnaires (n = 3,966 cases and n = 8,887 controls in the meta-analysis). Detailed definitions of cases and controls in cohorts are given in our previous publication 77 . We adjusted for age, sex, fasting status, lipid-modifying drugs and current smoking status.…”
mentioning
confidence: 99%